Assessment of insecticidal effects and selectivity of CAPA‐PK peptide analogues against the peach‐potato aphid and four beneficial insects following topical exposure. Issue 10 (27th July 2020) - Gui, Shun‐Hua; Taning, Clauvis NT; De Schutter, Kristof; Yang, Qun; Chen, Pengyu; Hamshou, Mohamad; Nachman, Ronald J; Pandit, Aniruddha A; Dow, Julian AT; Davies, Shireen; Smagghe, Guy
Abstract: BACKGROUND: Insect Capability neuropeptides (CAP2b/CAPA‐PKs) play a critical role in modulating different physiologies and behavior in insects. In a previous proof‐of‐concept study, the CAP2b analogues 1895 (2Abf‐Suc‐FGPRLamide) and 2129 (2Abf‐Suc‐ATPRIamide) were reported to reduce aphid fitness when administered by injection. In the current study, the insecticidal efficacy of 1895 and 2129 on the peach potato aphid Myzus persicae was analyzed by topical application, simulating a spray application scenario in the field. Additionally, the selectivity of the tested analogues was evaluated against a selection of beneficial insects, namely three natural enemies ( Adalia bipunctata, Chrysoperla carnea and Nasonia vitripennis ) and a pollinator ( Bombus terrestris ). RESULTS: Within 3–5 days post topical exposure of aphids to 1895, higher mortality (33%) was observed, as was the case for the treatment with 2129 (17%) and the mixture of 1895 + 2129 (47%) compared to the control (3%). 1895 and the mix 1895 + 2129 showed the strongest and comparable insecticidal effects. Additionally, surviving aphids treated with 1895 showed a reduction in total lifetime reproduction ( GRR ) of 30%, 19% with 2129 and 39% with the mix 1895 + 2129. Of interest from a biosafety perspective is that by using the same delivery method and dose, no significant effects on survival, weight increase and food intake was observed for the representative natural enemies and the pollinator. CONCLUSION: This study highlights the potential of exploiting CAP2b analogues such as 1895 (core structure FGPRL) as aphicides. Additionally, the CAP2b analogues used in this study were selective as they showed no effects when applied on four representative beneficial insects. Abstract : Using topical exposure, this study demonstrated CAPA‐PK analogues were effective in expediting aphid mortality and reducing reproduction, while remaining selective and non‐toxic to four representative beneficial insects. © 2020 Society of Chemical Industry